Initial Gamma Knife Radiosurgery for Large or Documented Growth Asymptomatic Meningiomas: Long-Term Results From a 27-Year Experience - Fu, Junyi; Wu, Lisha; Peng, Chao; Yang, Xin; You, Hongji; Cao, Linhui; Deng, Yinhui; Yu, Jinxiu (Frontiers in Oncology, 2020)
Objective: The aims of this study were to investigate the long-term outcomes of initial Gamma Knife radiosurgery (GKRS) for large (≥20 mm) or documented growth asymptomatic meningiomas. Design and Methods: This was a single-center retrospective study. Fifty-nine patients with large (≥20 mm) or documented growth asymptomatic meningiomas undergoing initial GKRS were enrolled. The median age was 56 (range, 27-83) years. The median time of follow-up was 66.8 (range, 24.6-245.6) months, and the median tumor margin dose was 13.0 Gy (range, 11.6-22.0 Gy). Results: Tumors shrunk in 35 patients (59.3%) and remained stable in 23 (39.0%). One patient (1.7%) experienced radiological progression at 54 months after GKRS. The PFS was 100%, 97% and 97% at 3, 5 and 10 years respectively. Nine patients (15.3%) occurred new neurological symptoms or signs at a median time of 8.1 (range, 3.0-81.6) months. The symptom PFS was 90% and 78% at 5 and 10 years respectively. Fifteen patients (25.4%) occurred peritumoral edema (PTE) at a median time of 7.2 (range, 2.0-81.6) months. One patient underwent surgical resection for severe PTE. In univariate and multivariate analysis, Only tumor size (≥25 mm) and maximum dose (≥34 Gy) were significantly associated with PTE (hazard ratio [HR]= 3.461, 95% confidence interval [CI]=1.157-10.356, p=0.026 and HR=3.067, 95% CI=1.068-8.809, P=0.037, respectively). Conclusions: In this study, initial GKRS can provide a high tumor control rate as well as an acceptable rate of complications in large or documented growth asymptomatic meningiomas. GKRS may be an alternative initial treatment for asymptomatic meningiomas.